Analysis of Connotative Meaning in Five Songs in the Album "Menari Dengan Bayangan" by Baskara Putra as Teaching Material in Poetry Learning - Debi Febianto; Asa Yuliara (Indonesian Journal of Innovation Multidisipliner Research, 2025)
Music, which involves sound and rhythm, is often used as a form of expression or entertainment, and song lyrics as a form of poetry have similar aspects to poetry, such as rhythm, rhyme, metaphor and emotional expression. In a song lyric, the connotation meaning, both positive and negative, is an important element in understanding the implied message in the song lyrics. This study uses a qualitative descriptive analysis method with a semantic content analysis approach to identify and classify connotative meanings in five songs, namely Membasuh, Secukupnya, Rumah ke Rumah, Efisiensi, and Untuk Apa / Untuk apa, which are included in the album "Menari dengan Bayangan" by Baskara Putra. The results of the analysis of the five songs can be calculated as follows: the song Membasuh found 16 or the equivalent of 16.33% of words or phrases containing connotative meaning. The second song, the song Secukupnya found 28 or equivalent to 16.18% of words or phrases containing connotative meaning. The third song, Rumah ke Rumah found 17 or equivalent to 7.69% of words or phrases containing connotative meaning. The fourth song, the song Efisiensi found 16 or equivalent to 16.33% of words or phrases containing connotative meaning. And the last song, the song Untuk Apa/ntuk apa found 44 or equivalent to 25.29% of words or phrases containing connotative meaning. Of the five songs that have been analyzed in general, there is an average percentage of words or phrases that contain connotative meaning of 15.5%